Cross-dehydrogenative coupling reaction using copper oxide impregnated on magnetite in deep eutectic solvents. Issue 3 (24th September 2015) - Marset, Xavier; Pérez, Juana M.; Ramón, Diego J.
Abstract : The synthesis of different tetrahydroisoquinolines using choline chloride : ethylene glycol as a deep eutectic solvent (DES) and copper(ii ) oxide impregnated on magnetite as a catalyst has been accomplished successfully. Abstract : The synthesis of different tetrahydroisoquinolines using choline chloride : ethylene glycol as a deep eutectic solvent (DES) and copper(ii ) oxide impregnated on magnetite as a catalyst has been accomplished successfully. The copper catalyst amount is the lowest loading ever reported. The presence of DES showed to be essential since the reaction in the absence of this medium did not proceed. A direct proportional relationship was found between the conductivity of DES medium and the yield obtained. The DES and the catalyst could be reused up to ten times without any detrimental effect on the yield of the reaction, with the aerobic conditions making the protocol highly sustainable, where the only waste is water.